Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Albert Watkins at viewing site of Chattanooga from atop Lookout Mountain Albert wearing his railroad cap and large sunglasses